Unpaid leave on COVID-19: The impact of psychological breach contract on emotional exhaustion: The mediating role of job distrust and insecurity - Qadri, Syed Usman; Li, Mingxing; Ma, Zhiqiang; Qadri, Safwan; Ye, Chengang; Usman, Muhammad (Frontiers in Psychology, 2022)
This research intends to increase awareness of the existence of psychological breach contracts on emotional exhaustion in the context of a prolonged COVID-19 pandemic, with the function of organizational distrust (OD) and job insecurity (JI) serving as mediating factors. We used partial least squares structural equation modeling (PLS-SEM) to look at the 437 questionnaires that private sector workers in Pakistan filled out during the COVID-19 outbreak. The findings of direct and indirect effects show that (PBC) psychological breach contract directly leads to emotional exhaustion (EH) and has a significant indirect relationship through job insecurity (JI). Moreover, psychological contract breach (PBC) directly leads to emotional exhaustion (EH) and has a significant indirect relationship through organization distrust (OD). The study shows both theoretical and practical implications, as well as areas where more research needs to be done.